Condition of the liver in patients with toxic cutaneous porphyria - Doğramacı, İhsan; Tınaztepe, Behçet; Günalp, Altan (The Turkish Journal of Pediatrics, 1962)
Clinical and laboratory findings in nineteen patients with toxic cutaneous porphyria revealed some derangement of liver function and enlargement of the liver in the majority of cases.In one case, examination of a liver biopsy specimen indicated the presence of chronic hepatitis and a resemblance to liver at the pre-cirrhotic stage was noted. Fluorescent microscopy of the same specimen showed diffuse red fluorescence of the parenchymal tissue but no fluorescence of normoblasts was seen in bone marrow from the same patient.These findings indicate to the authors that the current cases of porphyria in southeastern Turkey are of the hepatic type.